With socioeconomic status controlled, cigarette use is lower among American Indians/Alaska Natives than whites. (1st June 2020) - Cunningham, James K.; Ritchey, Jamie; Arambula Solomon, Teshia G.
Highlights: Higher crude prevalence of cigarette use among AI/AN than whites was examined. Race/ethnicity did not explain higher crude prevalence of use among AI/AN vs. whites. Lower socioeconomic status among AI/AN helped explain their higher cigarette use. When socioeconomic status was controlled, use was lower among AI/AN than whites. Socioeconomic status should be a focal issue in AI/AN cigarette prevention policy. Abstract: Background: Higher crude prevalence of cigarette use among American Indians/Alaska Natives (AI/AN) than non-Hispanic whites (NHW) has helped engender an assumption that race/ethnicity explains the difference. This study examines whether being AI/AN versus NHW predicts greater use when socioeconomic status and demographics are controlled. Methods: Data came from the National Survey on Drug Use and Health (2013–2017). Using logistic regressions with socioeconomic (income, education) and demographic (gender, age, marital status) controls, differences between AI/AN (n = 4, 305) and NHW (n = 166, 348) regarding heavier cigarette use (past month daily use, past month use of 300+ cigarettes, and nicotine dependence) and current cigarette use (past month use plus 100+ cigarettes in lifetime) were assessed. Adjusted predicted probabilities were also constructed. Results: NHW, compared to AI/AN, had greater odds of daily use: adjusted odds ratio (AOR) = 1.23 (95% CI: 1.03–1.49); predicted probabilities—15.3% and 13.0%, respectively. NHW had greater odds of using 300+ cigarettes: AOR = 1.47 (CI: 1.19–1.83); predicted probabilities—13.6% and 9.9%. NHW had greater odds of being nicotine dependent: AOR = 1.57 (CI: 1.31–1.89); predicted probabilities—10.3% and 7.1%. A difference in current use was not found. As controls, income and education were especially impactful. Conclusions: With controls, particularly for socioeconomic status, heavier cigarette use was lower among AI/AN than NHW, and a current cigarette use difference was not indicated. This contradicts the idea that being AI/AN versus NHW independently predicts greater cigarette use, and it underscores the importance of socioeconomic status for understanding cigarette use among AI/AN.